Statin Use in Metabolic Dysfunction-Associated Steatotic Liver Disease and Effects on Vibration-Controlled Transient Elastography-Derived Scores—A Population-Based Inverse Probability Treatment Weighting Analysis - Natchaya Polpichai; Sakditad Saowapa; Aunchalee Jaroenlapnopparat; Leandro Sierra; Pojsakorn Danpanichkul; Panisara Fangsaard; Phuuwadith Wattanachayakul; Apichat Kaewdech (Livers)
Background/Objectives: Metabolic dysfunction-associated steatotic liver disease (MASLD) is the leading cause of chronic liver disease globally. The impact of statins on liver fibrosis severity in MASLD individuals remains uncertain, despite their known cardiovascular benefits. Methods: A cross-sectional study was performed utilizing the National Health and Nutrition Examination Survey (NHANES) database from 2017 to 2018. MASLD was defined by hepatic steatosis (controlled attenuation parameter [CAP] score ≥ 288 dB/m) without other etiologies. Using inverse probability treatment weighting to minimize confounding, we examined the association between statin use and MASLD outcomes, including at-risk steatohepatitis (FibroScan-aspartate aminotransferase [AST] [FAST] score ≥ 0.67), significant and advanced fibrosis (liver stiffness measurement [LSM] ≥ 8.8 kilopascals [kPa] and ≥ 11.7 kPa), and advanced fibrosis (AGILE 3+ score ≥ 0.68). Results: Of 1283 MASLD patients, 376 were prescribed statins within the past 30 days. After adjustment for confounders, statin use was significantly associated with reduced risks of at-risk steatohepatitis, significant fibrosis, and high AGILE 3+ scores, with odds ratios (ORs) of 0.29 (95% CI: 0.01 to 0.87), 0.54 (95% CI: 0.31 to 0.95), and 0.41 (95% CI: 0.22 to 0.75), respectively. However, a subgroup analysis showed this effect persisted only with lipophilic statins. Conclusions: Statin use was associated with reduced steatohepatitis and fibrosis in patients with MASLD, supported by robust causal inference and vibration-controlled transient elastography-derived scores.